FUNCTIONAL IMPAIRMENTS OF GASTROINTESTINAL MOTILITY AND GASTROINTESTINAL TRACT MICROBIOTA - A.V. Malkoch; S.V. Bel'mer; M.D. Ardatskaya (Union of pediatricians of Russia, 2009)
Functional dysmotility is one of the most common evidence of pathology in gastrointestinal tract (GIT). GIT motility regulation is multilevel in nature at the level of central and peripheral nervous system, vegetative nervous system as well as locally directly in the intestinal tract. Gastrointestinal tract microbiota significantly contributes to the local regulation of motility both by forming fecal masses and secreting various metabolites, particularly short chain fatty acids whose composition and number depends on the nutritive factors of microbiota. For normal functioning and metabolism, saprophitic microbiota needs a significant number of undigestible carbohydrates, i.e. prebiotics. Prebiotics are an integral component of the complex therapy for functional impairments of gastrointestinal tract.Key words: gastrointestinal tract, motility, functional impairments, mictobiota, short chain fatty acids, prebiotics, lactulose.